TIPOLOGI DAN STRATEGI PENGEMBANGAN KESATUAN PENGELOLAAN HUTAN DI INDONESIA - Kushartati Budiningsih; Sulistya Ekawati; Gamin Gamin; Sylviani Sylviani; Elvida Yosefi Suryandari; Fentie Salaka (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2015)
Typology of Forest Management Unit (FMU) arranged through clustering based on its characteristics. These characteristics are FMU managers, participation of stakeholders and their business potential. The survey approach used by sending questionnaires to 86 FMU models that already have organization as primary data collection. Literatures are used as suporting data. Based on questionnaires collected from 35 FMU there are three types of FMU such as type A (index 3.66 -5.00), type B (index 2.33 to 3.66) and type C (index 1.00 to 2.33). The characteristics of type A are good understanding of FMU concept, sufficient number of employees and the employees have good capabilities, high stakeholders support, and good forest business potential. The characteristics of type B are enough understanding of the FMU concept, not enough employees and their capabilities, enough stakeholders support and there are forest business potential. The characteristics of types C are less understanding of the concept, the number and capability of human resources is not enough, lack of stakeholder support, and lack of forest business potential. Most FMUs (97%) belong to type B and type C. It means that the FMU still need assistance from the government in its development.